Analisis Penyelesaian Konflik Antara Dinas Perhubungan dengan Juru Parkir dalam Kebijakan Pembayaran Parkir Melalui QRIS di Taman Bungkul Kota Surabaya - Wahyu, Diky; Zacky, Mu'azari Khoirul; Erlangga, Mohammad Rafli; Illahi, Rizky Nizar Wahyu; Anisykurlillah, Rosyidatuzzahro (Ikatan Da'i Indonesia, 2024)
One of the problems that often arises in implementing new government policies is resistance from the community. This also happens to the parking payment policy via the QRIS (Quick Response Code Indonesian Standard) system at Taman Bungkul Surabaya. Although basically this policy aims to simplify and modernize the payment system, its implementation has actually triggered rejection from some people involved, including parking officers. This research aims to analyze how the conflict between the Transportation Service and parking officers is resolved in the parking payment policy via QRIS in Taman Bungkul, Surabaya City. The research method used is descriptive qualitative with interviews, documentation and data collection, and uses conflict resolution theory according to Ralf Dahrendorf which states that conflict resolution can be resolved in three ways, namely Arbitration, Mediation and Arbitration. The results of this research are to explain parking fees that have not reached the target, the application of QRIS for parking payments, conflicts of interest and policy evaluation, as well as digital transformation and socio-economic impacts.